Economics and culture - Throsby, C. D. (Cambridge, UK ; New York : Cambridge University Press, 2001)
Brings together two very disparate areas, considering both the economic aspects of cultural activity, and the cultural context of economics and economic behaviour. The author discusses how cultural goods are valued in both economic and cultural terms, and introduces the concepts of cultural capital and sustainability.
1. Introduction -- 2. Theories of value -- 3. Cultural capital and sustainability -- 4. Culture in economic development -- 5. Economic aspects of cultural heritage -- 6. The economics of creativity -- 7. Cultural industries -- 8. Cultural policy -- 9. Conclusions.
Includes bibliographical references.
Includes bibliographical references (pages 168-187) and indexes.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Economics -- Sociological aspects; Culture -- Economic aspects; Cultural industries -- Economic aspects; Cultural policy; Économie politique -- Aspect sociologique; Culture -- Aspect économique.; Industries culturelles -- Aspect économique.; Politique culturelle; POLITICAL SCIENCE -- Public Policy -- Cultural Policy; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE -- Popular Culture; Cultural policy; Culture -- Economic aspects; Economics -- Sociological aspects; Kultur; Wirtschaftswissenschaften; Cultuur; Economische aspecten; Économie de la culture; Sociologie économique.; Electronic books; Electronic books